Playful Disruption of Digital Media (Gaming Media and Social Effects,, 2018)
This book starts with the proposition that digital media invite play and indeed need to be played by their everyday users. Play is probably one of the most visible and powerful ways to appropriate the digital world. The diverse, emerging practices of digital media appear to be essentially playful: Users are involved and active, produce form and content, spread, exchange and consume it, take risks, are conscious of their own goals and the possibilities of achieving them, are skilled and know how to acquire more skills. They share a perspective of can-do, a curiosity of what happens next? Play can be observed in social, economic, political, artistic, educational and criminal contexts and endeavours. It is employed as a (counter) strategy, for tacit or open resistance, as a method and productive practice, and something people do for fun. The book aims to define a particular contemporary attitude, a playful approach to media. It identifies some common ground and key principles in this novel terrain. Instead of looking at play and how it branches into different disciplines like business and education, the phenomenon of play in digital media is approached unconstrained by disciplinary boundaries. The contributions in this book provide a glimpse of a playful technological revolution that is a joyful celebration of possibilities that new media afford. This book is not a practical guide on how to hack a system or to pirate music, but provides critical insights into the unintended, artistic, fun, subversive, and sometimes dodgy applications of digital media. Contributions from Chris Crawford, Mathias Fuchs, Rilla Khaled, Sybille Lammes, Eva and Franco Mattes, Florian 'Floyd' Mueller, Michael Nitsche, Julian Oliver, and others cover and address topics such as reflective game design, identity and people's engagement in online media, conflicts and challenging opportunities for play, playing with cartographical interfaces, player-emergent production practices, the re-purposing of data, game creation as an educational approach, the ludification of society, the creation of meaning within and without play, the internalisation and subversion of roles through play, and the boundaries of play.